Efficacy and safety of Chinese herbal medicine for metabolic conditions: a systematic review and meta-analysis of randomised controlled trials - Liang, Yinglin; Yu, Hongshen; Ren, Jie; Ren, Jiayi; Chen, Guanlin; Zhang, Yikai; Cai, Yefeng; Ni, Xiaojia (Frontiers in Pharmacology, 2026)
Background and purposeObservational studies indicate a high prevalence of dampness syndrome in metabolic diseases from the perspective of traditional Chinese medicine theory. This systematic review and meta-analysis aimed to assess the efficacy and safety of Chinese herbal medicine (CHM) for metabolic conditions via the therapeutic approach of eliminating dampness.Materials and methodsSix medical databases were searched up to August 2024 to identify randomised controlled trials (RCTs) involving individuals with type 2 diabetes mellitus (T2DM), hypertension, dyslipidaemia, or obesity, where the intervention included oral CHM targeting dampness. Risk of bias was assessed using the Cochrane Collaboration’s tool. Meta-analyses and forest plots were generated using Review Manager 5.3. Evidence quality was evaluated per the Grading of Recommendations Assessment, Development and Evaluation (GRADE).ResultsMeta-analyses of 122 RCTs (n = 11,252 participants) showed that dampness-eliminating CHM, when combined with lifestyle interventions, improved fasting plasma glucose (FPG), diastolic blood pressure (DBP), and body mass index (BMI), but exerted limited impacts on 2-h postprandial glucose (2hPG) and systolic blood pressure (SBP). When used as an adjunct to pharmacotherapy, CHM significantly enhanced reductions in FPG, 2hPG, SBP, and DBP. The effects of CHM on lipid profiles were modest and uncertain. Although dampness-eliminating CHM as a whole conferred benefits for obesity, no outstanding formula with robust evidence was identified. Across all included RCTs, no additional adverse events were observed compared to pharmacotherapy alone. Promising CHM formulae included Gegen Qinlian Decoction for diabetes and Banxia Baizhu Tianma Decoction for hypertension. Poria, derived from the sclerotia of Poria cocos (Schw.) Wolf., emerged as a key component across multiple conditions. Overall, while the meta-analysis suggested promising findings for dampness-eliminating CHM in modulating metabolic conditions, the certainty of evidence was limited due to heterogeneity and lack of blinding. Specifically, the quality of evidence for individual CHM formulae was unsatisfactory, as most studies were of small scale.ConclusionDampness-eliminating CHM may serve as a complementary therapy for metabolic diseases such as hypertension and diabetes. Further high-quality RCTs are required to confirm its role in dyslipidaemia and identify the most effective CHM formulae for obesity.